Do No Harm: the Extended Mind Model and the Problem of Delayed Damage - Williams, James (Sophia, 2016)
I argue in this essay that there can be harm due to philosophy that is not directly expressed in violent imagery. The harm is instead a concealed and delayed detrimental effect of an assumption of non-violence in a working model, defined as a picture of a field of enquiry and the methods required to approach it. Theses for the extended mind, as developed by Andy Clark and others, lead to a form of harm that follows from the models they work with. These engineering, tool and function-based models seek smooth interactions and transparency. Following points made by Kim Sterelny in the philosophy of biology, I argue that claims for smoothness and transparency conceal underlying conflict in the situations they seek to describe and explain. This concealment leads to harm, defined as a diminishing of our capacities to flourish in a given environment.